THE ACCRUAL PRINCIPLE APPLIED TO BANK ACCOUNTING. - Husband, W. H. (The Accounting Review, 1926)
Abstract The accrual method of accounting is commonly accepted as the most scientific and accurate method of handling accounts. Yet, in spite of this fact, a great many banks fail to realize the significance of the accrual principle. The accrual system is also especially valuable in affording an excellent check for the bank, and particularly so where the auditor or comptroller at the central bank wants to supervise the operations in the various departments of the main office and branch banks. This is the result of the fact that accruals must sooner or later be paid off in cash. At the same time, an accrual system that it is worth while to operate must be simple enough in application to be readily understood by the average bank clerk, comprehensive enough to cover all of the various operations in the banking business, and, most important of all, accurate enough to constitute an actual audit and control of the income and expense accounts. A satisfactory accrual system cannot be constructed overnight, but involves intensive and detailed study. It must not only provide for the accounting of accruals, but must also guard against undue duplication.